Estudio de viabilidad técnico financiera para la producción de tilapia en municipio de Tauramena Casanare para atender el mercado de la ciudad de Bogotá. (2022)
Colombia, due to its geographical and climatic conditions, is rich in water resources that are home to one of the products in great demand in the national and international market. This product is fish, which due to its characteristics and nutritional value, is one of the foods most desired by Colombians and Bogotans. The market study shows that the consumption of fish has had a significant growth in Colombia where between 1986 and 2020 its per capita consumption went from 1.7 kg to 8.8 kg per person in the year, which represents more than 400% during this period. The average annual consumption figures are very low, compared to the per capita consumption in the world, which is approximately 21 kilograms per year. Thus, the national government, through the Colombia Productiva program of the Ministry of Agriculture, aims to improve productivity, production quality and increase fish consumption among Colombians and spend 8kg – 19.8kg per person in the year, very similar to international standards.